Research trends in the development of learning models oriented to increasing scientific literacy: A systematic literature review - Romli, Sunaryo; Suhandi, Andi; Muslim, Muslim; Kaniawati, Ida (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to identify and analyze publications on the use of learning models, learning approaches, or learning programs in Science Education oriented towards enhancing scientific literacy based on research journal articles over the last five years from 2019 to 2024. A systematic literature review method was employed, guided by the PRISMA flowchart. Data were obtained from 456 national and international articles through Mendeley. After screening, 15 articles were found to meet the criteria as samples. Our findings indicate that integrated science education using a variety of models, approaches, or programs significantly improves students' scientific literacy. This study delineates effective educational strategies, impacting the pedagogical domain by offering insights into learning models that can foster scientific literacy. Future research should investigate the integration of inquiry-based collaborative learning with team-based projects to innovate and enhance educational outcomes.